Tandslipning och tandklippning på smågrisar - Wahlgren, Paulina (2016)
Piglets are born with so-called needle teeth which often routinely are cut or grinded. The reasons are that the economic benefit on the production should increase and that damages on both the sow and piglets decreases. Tooth resection means that parts of the original length of the tooth is removed by either tooth cutting or tooth grinding. The negative effects that occur by tooth resection can outnumber the positive effects, since tooth resection can lead to damages on teeth and gums and lead to behavioural disorders and stress to the piglets. The rate of facial injuries can be reduced but damages may still occur depending on resection method. Piglet survival can be influenced positively. A more uniform weaning weight is another possible positive effect, but it may as well be a reduced growth if the damage is too extensive to the piglet. It is more justified to apply tooth resection to reduce udder damage on the sow if she is held in a farrowing crate, but the same results can be achieved by a more suitable living environment such as not being fixated. The positive effects do not outweigh the negative under Swedish conditions so the motivations and reasons for tooth resection should be reconsidered.